A Compact High-Gain Coplanar Waveguide-Fed Antenna for Military RADAR Applications - Zaheer Ahmed Dayo; Qunsheng Cao; Yi Wang; Sandeep Pirbhulal; Ali Hassan Sodhro (International Journal of Antennas and Propagation)
This paper presents a new design of a compact, high-gain coplanar waveguide-fed antenna and proposes a multielement approach to attain enhanced characteristics. The proposed method overcomes the simulation and geometrical complexity and achieves optimal performance features. The antenna prototype is carefully designed, and simulation results have been analyzed. The proposed antenna was fabricated on a new WangLing TP-2 laminate with dimensions (0.195λ × 0.163λ × 0.0052λ) at the lowest resonance of 9.78 GHz. The results have been tested and experimentally verified. The antenna model achieved excellent performance including a peak realized gain better than 9.0 dBi, optimal radiation efficiency better than 87.6% over the operating band, and a good relative bandwidth of 11.48% at 10 dB return loss. Symmetrical stable far-field radiation pattern in orthogonal planes and strong distribution of current are observed. Moreover, a comparative analysis with state-of-the-artwork is presented. The measured and simulation result shows a good agreement. The high-performance antenna results reveal that the proposed model is a good contender of military airborne, land, and naval radar applications.